Postnatal consultations with an obstetrician after critical perinatal events: a qualitative study of what women and their partners experience - Marianne Johansen; Jette Led Sørensen; Stinne Høgh; Laura Emdal Navne; Mette Nordahl Svendsen (BMJ Open)
Objective The objective of this study was to explore women’s and their partners’ experiences with attending postnatal consultations with an obstetrician after critical perinatal events.Design Qualitative interview study. We did semi-structured individual narrative interviews exploring the lived experiences. Interviews were analysed using a phenomenological approach and the thematic analysis was validated by a transdisciplinary group of anthropologists, obstetricians and a midwife.Setting Department of obstetrics at a large hospital in Denmark.Participants We did a qualitative study with 17 participants (10 women and 7 partners) who had experienced critical perinatal events.Results Five major themes were identified: (1) a need to gain understanding and make sense of the critical perinatal events, (2) a need for relational continuity, (3) the importance of discussing emotional effects as well as physical aspects of occurred events, (4) preparing for future pregnancies and (5) closure of the story.Most of the participants emphasised the importance of knowing the obstetrician undertaking the postnatal consultation. The majority of the participants described a need to discuss the emotional effects of the experience as well as the physical aspects of occurred events. The postnatal consultation served as an approach to obtain a positive closure of their birth story and to feel confident about potential future pregnancies.Conclusions This interview-based study suggests that postnatal consultation with an obstetrician might be an important tool for women and their partners in understanding the course of events during the critical birth experience and in processing it and preparing for future pregnancies. It appears to be important to assign an obstetrician whom they already know and to encourage them to discuss not only physical aspects of what happened but also the emotional effects of the experience.